(untitled) (Sebha University Conference Proceedings, 2024)
Pressure buildup tests are one of the most common types of transient tests. In these tests, the well is produced at a constant rate for an extended period to achieve a stable pressure distribution, and then it is shut-in. Proper well shut-in is crucial as incorrect procedures can lead to inaccurate calculations. This study aims to interpret the pressure transient behavior in vertical wells that underwent pressure buildup tests for the bu-attifel field. The main objectives of the study involves analyzing the pressure buildup tests of three wells using KAPPA SOFTWARE, to estimate the permeability and skin factor for each well. Subsequently, the productivity index of each well is estimated using PROSPER SOFTWARE. Based on the derived parameters from the pressure buildup tests, the obtained results are compared with new production test data. Following that, a sensitivity analysis is performed for permeability and skin factor to diagnose the well condition and enhance productivity. We have obtained the results of the well-test analysis, and they are as follows: (A1=12.75 md), (A13=10 md), (A57=176 md). For permeability with positive skin factor values and the reservoir pressure, the results are: (5569 psi, 6232 psi, 6170 psi). Based upon the outcome, the productivity index for the wells was improved after comparing it with the new production test data. Sensitivity analysis was conducted to identify the factors influencing the productivity index of the wells.